POTENSI LIMBAH AIR TAHU ASAL KOTA MAROS SEBAGAI SUMBER BAKTERI PENGHASIL ENZIM PROTEASE DALAM MELAWAN RADIKAL BEBAS - Fitriana Fitriana; Amirullah Amirullah; Nurul Ilmy; Dyah Nur Pratiwi; Andi Adelah Resmilasari; Nabila Adelina HM (Fakultas Farmasi UMI, 2016)
This research aims to determine the protease enzyme-producing bacteria in Limbah Air Tahu and IC50 fermentat protease enzyme-producing bacteria in Limbah Air Tahu potentially fight free radicals. The methods in the study, which is taking Limbah Air Tahu and sewage treatment, followed by isolation of the bacteria producing the enzyme protease. Bacterial isolates obtained purified, for macroscopic examination. Fermentation bacteria and the production of protease enzymes. Purified protease enzyme obtained. Testing fermentat to fight free radicals with the DPP method and the determination of IC50 values fermentat protease enzyme-producing bacteria. The results of the protease enzyme producing bacteria identification on Biochemical activity test, there were 7 positive bacteria. The results of screening anti-free radical activity against isolates obtained 12 isolates with code FF 05. UMI IBPLT most excellent activity that is obtained of the IC50 fermentat isolates UMI IBPLT FF 05 is equal to 0.129 and dibandingakan denagn IC50 Vitamin C is = 14.81 + 0:10 then isolates FF 05 UMI IBPLT active in fighting free radicals.